Promoting English movie as a means of enhancing EFL learners’ cultural competence - Dwi Suny Wardhany (Journal of Applied Linguistics and Literature)
Very few studies discussing the use of English movies for the enhancement of EFL learners’ cultural competence in Indonesia. This study aims to describe the results of analyzing relevant research articles regarding the use of English movie/film for enhancing the cultural competence of EFL learners. This study was descriptive-qualitative. The data were taken from 7 (seven) research articles related to the study objective. In collecting the data (the research articles), the researcher conducted literature research or library research. It was carried out by searching, identifying, and selecting the research articles related to the study objective from electronic databases. Then, the data were analyzed by using qualitative data analysis which consists of data reduction, data display, and drawing the conclusion. The results showed that the seven research articles reported the enhancement of EFL learners’ cultural competence in terms of students’ attitude, knowledge, skills and cultural awareness. In addition, 3 research articles reported the enhancement of students’ language skills i.e., speaking, vocabulary, reading, and listening through learning activities done during and after watching and analyzing English movies. Therefore, it is suggested that English teachers pay attention to the culture teaching in ELT. English teachers can select appropriate English movie/film in the classroom as a means to enhance students’ cultural competence and to enhance students’ language skills.